Analisis yuridis putusan perkara sengketa ekonomi syariah di Pengadilan Agama Lamongan kelas IA tentang wanprestasi akad pembiayaan murabahah: Putusan nomor 0001/Pdt.GS/2021/PA.Lmg - Tarita, Yuanggi Nur Wiria; Yakin, Ahmad Ainul; Wati, Elia Hikma; Baihaqi, Imam; Sholihah, Mar’atus (Maliki Interdisciplinary Journal, 2023)
Default is the impact of unhealthy agreement. One of them is found in a sharia economic case in 2021 which was sued at the Lamongan Religious Court. This dispute was initiated because there was no good faith and non-fulfillment of achievements in the form of financing credit for one unit of car that should have been paid by the Defendant. For this reason, this research aims to understand and analyze the decision related to the dispute in more depth from a juridical perspective. The decision is a legal product of the Lamongan Religious Court in resolving sharia economic disputes related to default in the murabaha financing contract produced through a civil decision in a simple lawsuit No. 0001/Pdt.GS/2021/PA.Lmg. This research uses empirical legal research methods, by taking a jurisdictional location at the Lamongan Religious Court. This research uses primary, and secondary legal materials. The results of the discussion explain that the decision has a significant impact on sharia economic disputes in the Lamongan area. Based on the results of the decision analysis research, the judge granted the Plaintiff’s claim where the Defendant had defaulted on the Murabahah Financing Agreement No. 0326/ADDENDUM/05/2020/000219, dated 28-05-2020 and ordered to pay the remaining obligations.